The scientific production of medical students in Lima, Peru - Urrunaga-Pastor, Diego (2020)
Background Research is an important undergraduate competence for physicians. However, few studies have assessed the scientific production of medical students in Latin-America. Thus, this study had the objective to assess the rate and characteristics of research publications by undergraduate medical students in 2016, in Lima, Peru. Methods This cross-sectional study included all the students of the eight medical schools in Lima (Peru). The medical students included were collected from the registry of the National Medical Examination (taken during their last year of undergraduate studies) in 2016. To evaluate their research publications, systematic searches were performed in Google Scholar and PubMed during August 2018. Results We studied data from 1241 medical students (54.2% females) from eight medical schools. 173 (13.9%) students published at least one paper, 102 (8.2%) published at least one original paper, and 30 (2.4%) published at least one original paper in PubMed-Indexed journals. We registered a total of 174 papers authored by medical students, of which 98 (56.3%) were published in Peruvian journals, 128 (73.6%) were published in Spanish, 90 (51.7%) had a medical student as the first author, and 43 (24.7%) had a medical student as the corresponding author. The percentage of students with at least one publication was very heterogeneous across the eight medical schools evaluated (63.6%, 21.4%, 16.8%, 15.1%, 8.2%, 2.0%, 1.9%, and 0.0%). Conclusion Among medical students in Lima, one out of seven had published at least one paper, one out of 12 had published at least one original paper, and one out of 40 had published at least one original paper in PubMed-Indexed journals. Scientific production was very heterogeneous across medical schools.